Management of Ceratitis capitata (Diptera: Tephritidae) in Tunisian oases by mass trapping methods - Sameh Ben Chaaban; Abir Hafsi; Kamel Mahjoubi; Noureddine Nasr; Brahim Chermiti (Journal of Oasis Agriculture and Sustainable Development, 2022)
In Tunisia oases, the Mediterranean fruit fly (medfly) Ceratitis capitata affect heavily fruit production. The efficiency of the mass trapping technique based on the use of Cera Trap® was evaluated in two types of oases in the south of Tunisia against C.capitata. Our results showed that in the traditional oasis (mixed orchard), the medfly moves from one fruit specie to another according to their receptivity periods. The population density of medflies started low and peaked three times (16 Jun, 23 Jun, and 7 July) corresponding to the maturation period of apricot fig and peach fruits. The field study showed that medfly population density and rate of fruit damage were significantly lower in figs than in peaches and apricot. Modern oases have later apricot fruit maturity periods than traditional oases, and their medfly populations peaked at 19 Mai. Ceratrap® reduces 2, 2, and 6 times the population density of Mediterranean fruit fly and the rate of damaged fruits compared to untreated plots. These two parameters were twofold less in modern oases than in traditional oases. These results suggest that the use of traps at the density of 70 per ha is sufficient to protect crops under high population densities of C. capitata characterizing the traditional oases agricultural systems.